Handbook of International Negotiation 2014
DOI: 10.1007/978-3-319-10687-8_1
|View full text |Cite
|
Sign up to set email alerts
|

Representative Decision-Making: Challenges to Democratic Peace Theory

Abstract: It has become only too evident that traditional methods of confl ict prevention and resolution are no longer adequate or effective. This is why editor and contributor Mauro Galluccio's present volume appears to fi ll in an existing and ever more visible void in shaping an entirely new approach in modern-day diplomacy. The signifi cance of this book can hardly be over-rated. It offers an entirely new political and psychological angle to transforming confl ict by managing interpersonal dynamics and tailoring pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 216 publications
(319 reference statements)
0
8
0
Order By: Relevance
“…The role played by civil society groups around the negotiating table was also shown to influence DP. Using an HRM, Cuhadar and Druckman (2023) found that the key predictor of DP was ICs, one of seven civil society modalities. The HRM results showed that the ICs added significant variation to predictability based on PJ.…”
Section: Procedural Justice and Civil Societymentioning
confidence: 99%
See 1 more Smart Citation
“…The role played by civil society groups around the negotiating table was also shown to influence DP. Using an HRM, Cuhadar and Druckman (2023) found that the key predictor of DP was ICs, one of seven civil society modalities. The HRM results showed that the ICs added significant variation to predictability based on PJ.…”
Section: Procedural Justice and Civil Societymentioning
confidence: 99%
“…In this study, we focus on factors that influence durable societal peace (DP). Recent research has provided insights into the roles played by justice during the negotiation process (Druckman and Wagner, 2019) and civil society participation around that process (Cuhadar and Druckman, 2023). We found that adherence to principles of procedural justice (PJ) within the negotiation sets in motion a process that culminates in long-term peace.…”
Section: Introductionmentioning
confidence: 96%
“…The constraints come from constituencies (those being represented) and features of the other side in a negotiation. Of particular interest are the findings on constituencies divided into more hawkish or dovish factions (Aaldering & De Dreu 2012) and the type of regime, as autocratic or democratic, of the nation represented by the opponent (Cuhadar & Druckman 2014). The opportunities occur when representatives adopt a pro-social orientation, when they negotiate in privacy, when they have high status within the group being represented (increased latitude), and when salient solutions to problems are identified (Druckman 2015).…”
Section: Key Insightsmentioning
confidence: 99%
“…Thurstone’s Law of Comparative Judgment essentially states that such pairwise comparisons correspond to an internal, unknown utility scale (Thurstone, 1927). Recovering this hidden information from such qualitative preference is studied in various areas such as ranking theory (Marden, 1995), social choice theory (Rossi, Venable, & Walsh, 2011), voting theory (Coughlin, 2008), sports (Langville & Meyer, 2012), negotiation theory (Druckman, 1993), decision theory (Bouyssou et al, 2002), democratic peace theory (Cuhadar & Druckman, 2014), and marketing research (Rao, Green, & Wind, 2007). Thus, many results in preference learning are based on established statistical models for ranking data, such as the Plackett–Luce (Luce, 1959; Plackett, 1975) or Bradley–Terry (Bradley & Terry, 1952) models, which allow an analyst to model probability distributions over rankings.…”
Section: Behavioral Datamentioning
confidence: 99%